Physical activity and obesity - Bouchard, Claude; Katzmarzyk, Peter T., 1968- (Human Kinetics, 2010)
Addresses various topics that explore the links between physical activity (or inactivity) and obesity. This title examines obesity in different populations, including children and adults of various backgrounds, ethnicities and social classes. It presents an overview of the methods used in assessing the levels of sedentary behavior.